Participatory geographic information systems use in Copan Ruinas, Honduras: the development and evaluation of an environmental restoration public participatory Geographic Information System project - Johnson, James M. (Revista Geográfica de América Central., 2018)
Sustainable development is the challenge of the 21st century, and public administration will play a part in finding new ways of meeting human needs within the constraints of natural resource systems. The nature of sustainable development has led to expanded forms of governance and new partnerships among non-governmental organizations (NGOs), non-profits, and governments at all levels. This paper examines a participatory geographic information system project being developed in Copan Ruinas, Honduras and its effect on the community stakeholders. pecifically, the participatory geographic information system project will focus on the development of a geodatabase and usable maps that integrate: small-scale (less than five hectares on average) agroforestry projects, and highland habitat restoration projects. During this research, we will focus on the geographic information system project, public participation and how the project meets the standards of the International Association for Public Participation (IAP2) pillars of participation and core values.